Diagnostic Value of Bronchoalveolar Lavage in Sputum-Smear Negative Pulmonary Tuberculosis - Pokharel, Apar; Bhandari, Chhanya; Sharma, Bibek; Bhandari, Ramesh; Paudel, Yubraj (Journal of National Heart and Lung Society Nepal, 2023)
Introduction: Bronchoalveolar lavage has a high diagnostic utility for cytology and bacteriology. The aim of this study was to assess the diagnostic value of bronchoalveolar lavage (BAL) which underwent routine bronchoscopy for evaluation of lung disease. Materials and Methods: This is a hospital based descriptive study done from July 1, 2022, to June 30, 2023. Eighty bronchoalveolar lavage (BAL) cases were analyzed for differential count, cytological evaluation and bacteriological examination. All cases were included which were sent as BAL specimen to the laboratory department. Bronchoscopy was done as an outpatient procedure and lavage fluid obtained was analyzed. Result: Out of 80 cases, 51 were male and 29 were female. The age ranged from 10 to 80 years. The prevalence of tuberculosis in sputum smear negative cases was found to be 29%. Among 80 cases, eight cases were unsatisfactory, twenty-three cases were of tuberculosis, one case was of fungal infection, two cases were of malignancy, forty cases were of small airway infection and six cases were satisfactory but with no diagnostic value. Conclusion Bronchoalveolar lavage is valuable in diagnosis of tuberculosis, infections and malignancies.